Omega‐3 fatty acids deficiency aggravates glutamatergic synapse and astroglial aging in the rat hippocampal CA1. Issue 1 (27th November 2012) - Latour, Alizée; Grintal, Barbara; Champeil‐Potokar, Gaelle; Hennebelle, Marie; Lavialle, Monique; Dutar, Patrick; Potier, Brigitte; Billard, Jean‐Marie; Vancassel, Sylvie; Denis, Isabelle
Summary Epidemiological data suggest that a poor ω3 status favoured by the low ω3/ω6 polyunsaturated fatty acids ratio in western diets contributes to cognitive decline in the elderly, but mechanistic evidence is lacking. We therefore explored the impact of ω3 deficiency on the evolution of glutamatergic transmission in the CA1 of the hippocampus during aging by comparing 4 groups of rats aged 6–22 months fed ω3‐deficient or ω3/ω6‐balanced diets from conception to sacrifice: Young ω3 Balanced (YB) or Deficient (YD), Old ω3 Balanced (OB) or Deficient (OD) rats. ω3 Deficiency induced a 65% decrease in the amount of docosahexaenoic acid (DHA, the main ω3 in cell membranes) in brain phospholipids, but had no impact on glutamatergic transmission and astroglial function in young rats. Aging induced a 10% decrease in brain DHA, a 35% reduction of synaptic efficacy (fEPSP/PFV) due to decreased presynaptic glutamate release and a 30% decrease in the astroglial glutamate uptake associated with a marked astrogliosis (+100% GFAP). The ω3 deficiency further decreased these hallmarks of aging (OD vs. OB rats: −35% fEPSP/PFV P < 0.05, −15% astroglial glutamate uptake P < 0.001, +30% GFAP P < 0.01). This cannot be attributed to aggravation of the brain DHA deficit because the brains of OD rats had more DHA than those of YD rats. Thus, ω3 deficiency worsens the age‐induced degradation of glutamatergic transmission and its associated astroglial regulation in the hippocampus.